2019
DOI: 10.4269/ajtmh.19-0247
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Investigation of the Quality of Selected Medicines for Noncommunicable Diseases in Private Community Drug Outlets in Cambodia during 2011–2013

Abstract: Although the issue of substandard and falsified medicines is quite well known, most research has focused on medicines used to treat communicable diseases, and relatively little research has been carried out on the quality of medicines for noncommunicable diseases (NCDs). This study was designed to assess the quality of seven widely used medicines for NCDs in Cambodia during 2011-2013. Medicines were collected from private community drug outlets in Phnom Penh (urban area), by stratified random sampling and in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The results presented in this study demonstrate that 5.3% samples (95% CI, 0.021-0.086) were non-compliant (including all tested samples but excluding the falsi ed samples). The poor dissolution rates of the samples were a persistent problem, an observation which had previously been reported in our studies [56,57,60,61]. As an essential indicator of bioavailability and drug quality, the dissolution test has not been given as much attention as it deserves [58,62,63].…”
Section: Discussionmentioning
confidence: 48%
“…The results presented in this study demonstrate that 5.3% samples (95% CI, 0.021-0.086) were non-compliant (including all tested samples but excluding the falsi ed samples). The poor dissolution rates of the samples were a persistent problem, an observation which had previously been reported in our studies [56,57,60,61]. As an essential indicator of bioavailability and drug quality, the dissolution test has not been given as much attention as it deserves [58,62,63].…”
Section: Discussionmentioning
confidence: 48%
“…However, the presence of SFMs poses significant risks to individuals, such as lost treatment opportunities, treatment failures, and they could even be life-threatening ( Rahman et al, 2018 ). We have also reported that poor quality antibiotics have been detected in the common pharmaceutical market in a LMIC ( Yoshida et al, 2014 , Islam et al, 2017 , Khan et al, 2013 , Rahman et al, 2019 ). Although most medicines were of good quality, some of these have been intentionally falsified, while others have been unintentionally degraded.…”
Section: Discussionmentioning
confidence: 87%
“…3 ), were all of foreign origin, which may suggest that medicines can enter the country through unauthorized channels. The authenticity of the products and legitimacy of the manufacturers remained unclear due to the poor responses to our questionnaire (Supplemental Files S1 and S2 ) from both manufacturers and medicine regulatory authorities (Table 3 ), as observed previously [ 17 , 38 , 39 ]. A possible explanation of the low response in the former case might be that manufacturers are already aware that their products are of low quality.…”
Section: Discussionmentioning
confidence: 97%